Assessing the Role of Intraluminal Thrombus in Abdominal Aortic Aneurysm Biomechanics through Patient-Specific Bayesian Material Calibration - Caruso, Gaia; Guala, Andrea; Dux-Santoy, Lydia; Teixidó-Turà, Gisela; Rodriguez-Palomares, José Fernando; Bellmunt, Sergi; García-Reyes, Marvin; Martínez, Miguel Angel; Peña Baquedano, Estefanía (Jornada de Jóvenes Investigadores del I3A, 2025)
This study proposes a patient-specific material calibration framework to accurately characterize both aortic wall and intraluminal thrombus (ILT) properties. By integrating imaging and biomechanics, it enables reliable assessment of ILT’s mechanical role—often neglected in literature—thus avoiding stress overestimation and improving rupture risk evaluation in abdominal aortic aneurysm (AAA) models.